2016
DOI: 10.1053/j.jrn.2015.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Problems in Following the Hemodialysis Diet and Their Relation to Energy and Nutrient Intakes: The BalanceWise Study

Abstract: Objective To identify the problems experienced by hemodialysis (HD) patients in attempting to follow the HD diet, and their relation to energy and nutrient intakes. Design Cross-sectional analysis of baseline data from the BalanceWise Study. Setting Community-dwelling adults recruited from outpatient HD centers. Subjects After excluding participants with incomplete dietary analyses (n = 50), 140 community-dwelling African American and white (40/60%) men and women (52/48%) on chronic intermittent HD for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
60
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 17 publications
1
60
0
6
Order By: Relevance
“…replacing tomatoes in spaghetti or chili), and the vigilance required to follow the many components of the renal diet (low-salt, low-phosphorus, low-potassium, high-protein), may overwhelm patients causing them to either give up, or to adopt a very simple diet from which they derive little pleasure or nutrition. When asked about factors that make adherence to the HD diet difficult (rated ≥3 on a 5-point Likert scale), many BalanceWise participants reported that the diet is bland and tasteless (59/140) and too complicated (49/139), and that it is hard to keep track of nutrient intakes (64/140) 49 . In addition to potentially impairing nutrition status and quality of life 50 , advising HD patients to limit or avoid many plant-based foods, especially fruits and vegetables, may contribute to adverse metabolic states (e.g., oxidative stress, inflammation, metabolic acidosis, dyslipidemias) and conditions (e.g., constipation, hypertension) that negatively impact the health of HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…replacing tomatoes in spaghetti or chili), and the vigilance required to follow the many components of the renal diet (low-salt, low-phosphorus, low-potassium, high-protein), may overwhelm patients causing them to either give up, or to adopt a very simple diet from which they derive little pleasure or nutrition. When asked about factors that make adherence to the HD diet difficult (rated ≥3 on a 5-point Likert scale), many BalanceWise participants reported that the diet is bland and tasteless (59/140) and too complicated (49/139), and that it is hard to keep track of nutrient intakes (64/140) 49 . In addition to potentially impairing nutrition status and quality of life 50 , advising HD patients to limit or avoid many plant-based foods, especially fruits and vegetables, may contribute to adverse metabolic states (e.g., oxidative stress, inflammation, metabolic acidosis, dyslipidemias) and conditions (e.g., constipation, hypertension) that negatively impact the health of HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Further, choosing foods prepared without phosphorus additives may increase food costs by ~$2.00/day 20 . While cost may not be a deterrent for some patients, roughly one-third of HD patients in the BalanceWise study reported that their income did not meet their needs (32%), and/or that they had difficulty affording a healthy diet in the previous two months (39%) 24 .…”
Section: Restricting Dietary Phosphorus Intakementioning
confidence: 99%
“…As an added benefit, this approach limits commercially-prepared foods, which tend to be high in sodium 21,23,26 , and wet cooking methods also help remove potassium from foods 27 . Unfortunately, preparing meals from scratch is not the cultural norm in many regions facing high incidence rates of CKD, and may be difficult to sustain, particularly given that most HD patients report being too tired to cook (59%) 24 .…”
Section: Restricting Dietary Phosphorus Intakementioning
confidence: 99%
See 1 more Smart Citation
“…It should come as no surprise that the quality of the diet of CKD patients is suboptimal. [1][2][3][4] This may be explained by a myriad of factors, including financial and social barriers often linked to CKD, an emphasis on restriction of sodium, potassium, and phosphorous at the expense of compromising overall diet quality, [5][6][7] and simply global dietary changes toward western diets, with convenience, fast, and ultra-processed foods. In the recent years, through observational studies, we are learning that dietary quality may also influence the fate of patients with CKD.…”
Section: Y Ou Are Whatyou Eat the American Nutritionistmentioning
confidence: 99%